2005 International Symposium on Empirical Software Engineering, 2005.
DOI: 10.1109/isese.2005.1541842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pair programming at the development team level: an experiment

Abstract: We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 21 publications
2
28
1
1
Order By: Relevance
“…Through empirical research, Vanhanen and Lassenius illustrated that pair programming affects project attributes like: Project productivity, design quality, effort estimation and knowledge transfer within the team (Vanhanen and Lassenius, 2005). Similarly, from an academic perspective, there is an absolute need to evaluate the above mentioned attributes and determine exact ways to capitalize upon the same.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through empirical research, Vanhanen and Lassenius illustrated that pair programming affects project attributes like: Project productivity, design quality, effort estimation and knowledge transfer within the team (Vanhanen and Lassenius, 2005). Similarly, from an academic perspective, there is an absolute need to evaluate the above mentioned attributes and determine exact ways to capitalize upon the same.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Programming students agree that they have more confidence in their final solution when it is achieved through pair programming , and perceived pair programming as being valuable to their learning (VanDeGrift, 2004). The process of pair programming leads to students who are more satisfied with their work regardless of their ability and grade-level (Kavitha & Ahmed, 2013;Vanhanen & Lassenius, 2005), and who are more self-sufficient. The student perception of pair programming on various tasks was examined by Chaparro, Yuksel, Romero, and Bryant (2005), who reported that when considering program comprehension, refactoring and debugging, students were effective across all three.…”
Section: Introductionmentioning
confidence: 99%
“…[1] A global survey of the adoption of various development practices reported that 35% of development projects used PP [2]. The interest in PP is natural because PP can have a positive effect on, e.g., quality of code and design, knowledge transfer, learning, team work, and work satisfaction [3,4,5]. The negative effects can be increases in development effort [3,4,6,7] and mental exhaustiveness of work [1,8].…”
Section: Introductionmentioning
confidence: 99%